Comparison of Color Doppler US and CT Portography in Evaluating Portal Hypertension in Children - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2012)
Objectives: To compare grayscale and color Doppler ultrasound (CDUS) findings to that of multidetector computed tomography (MDCT) portography in the evaluation of portal hypertension in children. Methods: Thirty children (mean age, 11.4 years) with definitive clinical and laboratory diagnoses of portal hypertension were included in the study. Liver parenchymal changes, portal vein thrombosis, cavernous transformation, splenomegaly, recanalization of the paraumbilical vein, ascites collateral vessels, and hemodynamic parameters were evaluated prospectively. Results: Liver parenchymal heterogeneity (n = 21) was detected more often by CDUS than MDCT (P = 0.002). CDUS and MDCT established similar results for increased right/left lobe ratio, lobulation of the liver contour, ascites, and splenomegaly. Portal vein thrombosis, cavernous transformation, and recanalization of the paraumbilical vein were comparable between CDUS and MDCT (kappa = 1, P < 0.01). Collaterals were detected more by MDCT portography than by CDUS. Esophageal collaterals and azygous vein dilatation were seen only by MDCT portography (P < 0.01, P = 0.024; respectively). Conclusions: CDUS was superior to MDCT in identifying parenchymal changes and hemodynamic parameters. MDCT was superior in detecting abnormal collateral circulation. The combination of these two modalities provides more comprehensive information than either alone in the diagnosis and follow-up of portal hypertension.
Keywords: child; collaterals; color Doppler ultrasound; multidetector computed tomography; portal hypertension; COMPUTED-TOMOGRAPHY; VENOUS SYSTEM; COLLATERALS; SONOGRAPHY; ULTRASOUND; DIAGNOSIS; CIRRHOSIS; VEIN